Modern Pension System in Azerbaijan: Challenges and Reforms - Bitinas, Audrius (Teisė, 2018)
The aim of this article is to define the legislationAzerbaijan state social security pension system and latest reforms, influenced by the recent economic crisis and demographic – social challenges, and to provide with the conclusions in the state social guarantees context. In this paper author analyses challenges and presents conclusions and recommendations for further pension system reforms in Azerbaijan.